Extensive nitrogen loss from permeable sediments off North‐West Africa. Issue 4 (24th April 2016) - Sokoll, Sarah; Lavik, Gaute; Sommer, Stefan; Goldhammer, Tobias; Kuypers, Marcel M. M.; Holtappels, Moritz
Abstract: The upwelling area off North‐West Africa is characterized by high export production, high nitrate and low oxygen concentration in bottom waters. The underlying sediment consists of sands that cover most of the continental shelf. Due to their permeability sands allow for fast advective pore water transport and can exhibit high rates of nitrogen (N) loss via denitrification as reported for anthropogenically eutrophied regions. However, N loss from sands underlying naturally eutrophied waters is not well studied, and in particular, N loss from the North‐West African shelf is poorly constrained. During two research cruises in April/May 2010/2011, sediment was sampled along the North‐West African shelf and volumetric denitrification rates were measured in sediment layers down to 8 cm depth using slurry incubations with 15 N‐labeled nitrate. Areal N loss was calculated by integrating volumetric rates down to the nitrate penetration depth derived from pore water profiles. Areal N loss was neither correlated with water depth nor with bottom water concentrations of nitrate and oxygen but was strongly dependent on sediment grain size and permeability. The derived empirical relation between benthic N loss and grains size suggests that pore water advection is an important regulating parameter for benthic denitrification in sands and further allowed extrapolating rates to an area of 53, 000 km 2 using detailed sediment maps. Denitrification from this region amounts to 995 kt yr −1 (average 3.6 mmol m −2 d −1 ) which is 4 times higher than previous estimates based on diffusive pore water transport. Sandy sediments cover 50–60% of the continental shelf and thus may contribute significantly to the global benthic N loss. Key Points: High benthic N‐loss rates from permeable sediments underlying an upwelling area Benthic N‐loss rates increase with sediment permeability and grain size Extrapolated N‐loss rates amount to 995 kt N per year for an area of 53, 000 km 2